Advertisement-Financed Credit Ratings - Christian Siemering (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Traditional business models of credit rating agencies (CRAs) are criticized for creating incentives for misreporting. This paper investigates a potential alternative in which CRAs receive revenue from advertisement only. We use a two-period Bayesian reputation model and show that CRAs will shirk when their reputation is either very high or very low. When reputation is at a medium level, the prospect of exploiting better reputation in the future might discipline CRAs to exert high effort in the present. However, when misreporting is possible, the CRA will always shirk and conduct either rating inflation or deflation with positive probability.
Keywords: G24; D82; L15; 330